After the revelation: A brief exercise of legal imagination for humanity discover that it is not alone in the universe - Chiri Márquez, Renzo (2019)
This paper proposes an exercise of legal imagination in the event that something so spectacular and unexpected, such as the visit of an intelligent alien civilization, takes place, and ends by making us understand that we are not alone in this universe. This exercise includes a glimpse of how, in the face of the collapse of old paradigms and systems, the discipline of Law can contribute both to the establishment of different types of relations with extraterrestrial visitors, as well as in the construction of the new human civilization.